PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS LIVEWORKSHEET PADA KONTEN NUMERASI KERAJAAN MARTAPURA UNTUK SISWA KELAS VII SEKOLAH MENENGAH PERTAMA - Panduwena, Maidini; Kurniawan, Kurniawan (Program Studi Pendidikan Matematika FKIP Universitas Islam Darul Ulum, 2024)
This research aims to produce a learning media based liveworksheet on the contents of the Martapura Kingdom numeration with the ADDIE development model without the Evaliation stage. In the analysis phase, through the needs analysis 91.4% of students were very interested in studying the ancient numbers of the Martapura kingdom. Moreover, if the antique numbers of this kingdom are using a learning medium based on liveworksheet, where 82.8% of students are very interested using liveworksheets. At the design stage, the design phase is the planning phase of learning media that includes compiling learning objectives, making videos and planning learning media using the canva application. At the development phase, creating and developing learning media from all the components that have been prepared into an integral unity using liveworksheet. Once done, validation by material experts and media experts. The evaluation by historical material experts is 91.43%, and the average score by 3 validators mathematical materials experts is 85%. The assessment of media experts obtains the average rating by 3 medial expert validators is 87.2%. At the implementation stage, a small scale test is carried out to 10 pupils. After performing the test, the student was asked to fill in the prepared response lift. Based on the results of the study, it can be concluded that the product has been produced as a learning media based on liveworksheet on the contents of the king's numeration martapura for students of grade VII First High School has met the criteria very valid and very practical.